Paradigma Fiqh Sosial atas Kemiskinan dan Ikhitiar Pemberdayaan Ekonomi Ummat - A. Zaenur rosyid; Siti Sulikhah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2017)
To day, fiqh be present by way of progressive concept and responsive to change ages than just for the sake normative-dogmatic concept. Social fiqh is represent kiai Sahal well to do spark of socio-movement and become course build up alternative on the communities more than productive, self employed and prosperous so that balance of life on the whole world and the beyond (sa’adatuddarain) can be achieve in a use manner. Kiai Sahal pass through collective measure, system approach and constituted group to be rejoinder proverty problem in center of communities. Kiai Sahal was applied ijtihad jama’i as islamic lessons in light of legal status on multi problem is in proverty. Though in empowering approach on the grounds of bottom-up, kiai Sahal established in a BPR, BPPM included zakat as tools a proverty tackling for the moment.